Dependence of Piezoelectric Discs Electrical Impedance on Mechanical Loading Condition - Gogoi, Niharika; Chen, Jie; Fischer, Georg; Kirchner, Jens (Sensors, 2022)
Inthis paper, we study the electrical impedance response of different sizes of commercial piezoelectricdiscs for a wide range of frequencies (without and with mechanical load for0.1–1000 kHzwithresolution 20 Hz).The piezoelectric effect, along with its associated materials, fascinated researchers in allareas of basic sciences and engineering due its interesting properties and promising potentials.Sensing, actuation, and energy harvesting are major implementations of piezoelectric structures instructural health monitoring, wearable devices, and self-powered systems, to name only a few. Theelectrical or mechanical impedance of its structure plays an important role in deriving its equivalentmodel, which in turn helps to predict its behavior for any system-level application, such as withrespect to the rectifiers containing diodes and switches, which represent a nonlinear electrical load. Inthis paper, we study the electrical impedance response of different sizes of commercial piezoelectricdiscs for a wide range of frequencies (without and with mechanical load for0.1–1000 kHzwithresolution 20 Hz). It shows significant changes in the position of resonant frequency and amplitudeof resonant peaks for different diameters of discs and under varying mechanical load conditions,implying variations in the mechanical boundary conditions on the structure. The highlight of ourwork is the proposed electrical equivalent circuit model for varying mechanically loaded conditionswith the help of impedance technique. Our approach is simple and reliable, such that it is suitable forany structure whose accurate material properties and dimensions are unkno
Keywords: piezoelectric; impedance; electrical model; wide-range frequency

Electronic Circuits for Piezo electric Energy Harvesting and Sensor Array Systems - Gogoi, Niharika (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)
This thesis is a comprehensive study of piezoelectric energy harvesting circuits in response to human gait. The main goal of this work is to take advantage of ambient mechanical vibration to power a gait based wearable device integrated in a shoe. Most wearable devices are battery operated,which is followed by unsustainable course of action as the battery life expires. To meet the growing demand of wearable devices with environment friendly approaches, walking is one of the ways. The stress generated from walking has the potential to convert mechanical energy into electrical energy via piezoelectric elements. In this work, the piezoelectric element is used not only as an energy harvester but also as a sensor. We take advantage of the foot-strike to collect gait information and obtain electrical energy simultaneously. This brings a paradigm shift from wrist-based wearables to foot-based wearables. There are several energy harvesting circuits discussed in this work to under stand their response to a gait signal. The circuits studied were standard energy harvesting circuit (SEH), Self-powered Parallel Synchronous Switch Harvesting on Inductor (sp-p-SSHI), Self-powered Synchronous Electric Charge Extraction (sp-SECE), Self-powered Optimized Synchronous Electric Charge Extraction (sp-OSCE) and Full wave Voltage Doubler (VD), and then implemented in the proposed shoe application. Their working principles are assessed and rated against the used case of gait-excited piezoelectric elements. The advantages and disadvantages of these circuit topologies incorporating non-linear techniques are also discussed. Thesystem based-investigation is presented discussing the power consumption of each stage from sensor data collection to data transmission. Athorough analysis of the extent to which piezoelectric elements can contribute to the application with and without battery is presented in this thesis. The role of battery as back-up in simultaneous sensing and energy harvesting is also investigate

Energy harvesting from a piezo buzzer with Schottky diode and complementary MOSFET full-bridge rectifiers - Gogoi, Niharika; Kirchner, Jens; Fischer, Georg (2022 IEEE International Symposium on Applications of Ferroelectrics (ISAF), 2022)
In our paper, we have taken advantage of human walking on piezoelectric element and rectified the generated voltage through two types of rectifiers: standard rectifier (SR) and complementary MOSFET rectifier (CMOS-R). For a symmetric voltage signal, CMOS rectifier has always been a better choice than any diode based rectifier. However, in our work, it was observed that the SR gave higher output voltage levels than the CMOS-R <br
Keywords: PZT; energy harvesting circuit; rectifier

Insole Gait Acquisition System Based on Wearable Sensors - Gogoi, Niharika; Fischer, Georg; Kirchner, Jens; Yu, Zixuan; Qin, Yichun (Engineering Proceedings, 2021)
Human gait analysis is a growing field of research interest in medical treatment, diagnosis, sports training, and structural health monitoring. It is the study of graphical representation of human motion through observation method (video or image-based) in a clinical setup or placing sensor method at different parts of the body, to understand the condition of human muscles, mechanics, and fitness. Out of the two methods, the role of wearable sensors in such clinical applications is crucial because of their low cost, simple implementation, and time to time monitoring. In our study, we propose an insole design for wearable sensors based on lead zirconate titanate piezoelectric discs (PZT) and inertial measurement unit (IMU) BMI270 to acquire the human gait. A PZT and an IMU aligned on the same axis are placed in a metallic structure. Such structures are placed at three points of a shoe sole: toe, metatarsal, and heel. The human gait obtained from this insole layout is significantly affected by plantar pressure distribution and alignment of the feet. The PZT sensors give an insight into the pressure map under the feet in the form of voltage. The accelerometer in the IMU gives the change of position of the feet to examine the gait analysis. The gyroscope in IMU is used for the understanding of the motion and posture of feet by measuring its angular rate. The acquired data from these sensors shows that each individual has a different gait pattern at the three points in the sole. It also shows intra-individual variations where the gait of the same person varies in daily situations.<br

Simultaneous Step Counting and Energy Harvesting from Piezoelectric Discs Embedded in a Shoe - Gogoi, Niharika; Kirchner, Jens; Fischer, Georg; Zhu, Yuanjia (IEEE Sensors, 2022)
The main goal of this paper is to demonstrate that simultaneous sensing and energy harvesting from a piezoelectric element is feasible, instead of two separate systems, which ensures savings on cost and complexity. In our work, two types of interface circuitry to harvest energy from multiple piezoelectric elements embedded in a shoe are analysed. The harvested output is utilized to perform step counting of the subject wearing it.
Keywords: piezoelectric; sensing; wearable; energy harvesting; shoe; circuit